Calcium, magnesium and aluminium ions as decontaminating agents against dermal fluoride absorption following hydrofluoric acid exposure. (March 2021) - Vijayan, Suvarna Mini; Göen, Thomas; Dennerlein, Kathrin; Horch, R.E.; Ludolph, I.; Drexler, Hans; Kilo, Sonja
Abstract: The fluoride ions of the industrially largely irreplaceable, locally corrosive hydrofluoric acid (HF) can scavenge cations in biological tissues, which explains their high toxic potential, and also leads to local acidification through proton release. The influence of three complexing agents, calcium ( Ca 2+ ) gluconate (as 2.5% Ca 2+ gel and individually (2.84%) or commercially (10%) formulated Ca 2+ solution), magnesium ( Mg 2+ ) gluconate (2.84%) solution and aluminium ( Al 3+ ) solution (Hexafluorine®, pure and diluted) on the absorption of fluoride following HF exposure (1–3 min, 100 μl, 30%/0.64 cm 2 ) through human skin was investigated in an ex-vivo diffusion cell model. Fluoride absorption was assessed over 6–24 h and analysed with a fluoride electrode. Decreasing the contamination time reduced the fluoride absorption distinctly which was further reduced by the application of fluoride-binding decontamination agents ( Ca 2+, Mg 2+, Al 3+ ) or water alone without being significantly different. Ca 2+ appeared slightly more effective than Mg 2+ in reducing fluoride absorption. Moreover, the addition of pH adjusting buffer promoted the decontamination efficacy. Fluoride-binding agents can facilitate the decontamination of dermal HF exposure. However, prompt decontamination appeared to be the key to successful limitation of fluoride absorption and pushes the choice of decontamination agent almost into the background. Highlights: Immediate decontamination proved to be crucial to limit fluoride absorption. All decontamination strategies and water alone reduced dermal fluoride absorption. Buffer capacity may account for efficiency differences between decontaminants.